2019
DOI: 10.13075/mp.5893.00827
|View full text |Cite
|
Sign up to set email alerts
|

Cytostatic and cytotoxic waste – rules of conduct in Poland

Abstract: Polska jest jednym z krajów europejskich, w których wytwarza się najwięcej niebezpiecznych odpadów medycznych. Mimo że w Europie ilość produkowanych odpadów cytotoksycznych i cytostatycznych (stosowanych w chemioterapii przez chorych onkologicznie) od kilku lat się zmniejsza, w Polsce-rośnie. Odpady te stanowią zagrożenie bezpieczeństwa dla pracowników medycznych oraz chorych otrzymujących leki. Dlatego wymagane są specjalne procedury postępowania, które pozwalają ograniczyć szkodliwość tych leków dla zdrowia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Actually, ADs contamination in hospital environments and on equipment is the consequence of their massive use [17,18]. Moreover, patients can carry ADs contamination in domestic scenarios [19], and it eventually involves not only surfaces in the house environment but also the soil and superficial water [20]. Hamscher et al [21] have shown that there might be a potential contamination risk when administering ADs in veterinary medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, ADs contamination in hospital environments and on equipment is the consequence of their massive use [17,18]. Moreover, patients can carry ADs contamination in domestic scenarios [19], and it eventually involves not only surfaces in the house environment but also the soil and superficial water [20]. Hamscher et al [21] have shown that there might be a potential contamination risk when administering ADs in veterinary medicine.…”
Section: Introductionmentioning
confidence: 99%